فاعلية التشبيه البليغ في تشكيل الصور الشعرية: أشعار شوقي الوطنية أنموذجا - Mohammed Hafeez (Al-Zahra : Journal for Islamic and Arabic Studies, 2022)
The poetic image is one of the most important critical issues in literary studies as the effectiveness of poetry depends on images that highlight feelings and emotions, while simile is one of the most prominent devices through which the imagination appears, which contributes to the formation of the literary image. Furthermore, the eloquent simile is represented in the highest level in terms of artistic value, since the deletion of the particle (أداة التشبيه) and the point of similarity (وجه الشبه) gives the illusion that the topic (المشبه) and the image (المشبه به) are similar, as there is no distinction between them. This study aims to introduce the poet Ahmed Shawky, whose national character has changed between the stages he went through in his life, to discuss the term poetic image and its patterns, and finally to illuminate the main objective, which is the study of the eloquent simile and its effectiveness in forming literary images in national poems in which the poet Shawqi addressed the issues, problems, and hopes of his homeland, by concentrating on the patterns and sources of eloquent simile, as well as the relationship between the two sides of the simile, by using the descriptive analytical approach to explain the poet's personality and analyze his nationalistic poems, and the artistic approach to extract the artistic values related to the eloquent simile. The study concluded several results, one of which is that the poet invested the most prominent forms of eloquent simile informing the images, even though the pattern in which the image is the predicate of the subject or prefixed to the topic appears more commonly in Shawqi's national poems, and the form in which the image is the circumstantial adverb seems less frequently, besides other forms recorded in the average. The poet derived most of the images from natural manifestations while he picked up some of them from human and his organs, the tools that he uses, and cultural sources and religious meanings. In terms of the relationship between topic and image, the poet preferred to link the sensible to the sensible rather than the nonsensible to the nonsensible. In addition, his creativity appeared in the transformation in which the sensible was likened to the nonsensible, where he used the TashkhÊs and ThajsÊm techniques in several models.